2016
DOI: 10.30979/rev.abeno.v15i4.208
|View full text |Cite
|
Sign up to set email alerts
|

Comparação dos métodos tradicional e ativo de educação no aprendizado de um tema de Oclusão Dentária

Abstract: RESUMOEste trabalho avalia o efeito dos métodos de ensino tradicional e ativo aplicados ao conteúdo "montagem de modelos em articulador semiajustável (ASA)". Trata-se de um estudo transversal em relatórios de 49 alunos da disciplina de Oclusão, divididos aleatoriamente em dois grupos de atendimento mútuo em duplas. O grupo 1 (n=26) recebeu um artigo sobre o tema e as dúvidas foram resolvidas em debate, o grupo 2 (n=23) participou de aula expositiva seguida das práticas. Os dados foram compilados quanto às taxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Participants also noted that lecture accompanying questions and answers is a better approach in CME, but a pre-test (pre-test (preliminary exam before the lecture)) is not necessary. Previous studies have confirmed that collaborative, cooperative, and problem-based teaching methods are more effective in enhancing lifelong learning; it is also considerably better to replace traditional methods in continuing education programs (19)(20)(21).…”
Section: Discussionmentioning
confidence: 95%
“…Participants also noted that lecture accompanying questions and answers is a better approach in CME, but a pre-test (pre-test (preliminary exam before the lecture)) is not necessary. Previous studies have confirmed that collaborative, cooperative, and problem-based teaching methods are more effective in enhancing lifelong learning; it is also considerably better to replace traditional methods in continuing education programs (19)(20)(21).…”
Section: Discussionmentioning
confidence: 95%